The social function of cooperative: comparative law notes - Fici, Antonio (REVESCO. Revista de Estudios Cooperativos, 2015)
Many Constitutions around the world attribute a social function to cooperatives and provide for their promotion by the law. The law and the European institutions include cooperatives among the entities of the social economy, which the State has the duty to support. For these provisions to be legitimate with regard to the constitutional principle of equal treatment by law, cooperatives must have a legal identity different from that of other business organizations. This article aims at identifying the principal elements of the legal identity of a cooperative, which make it a type of society worth of a specific protection and privileged treatment in the Constitution and the law. The article will also discuss the distinction between mutual cooperatives and general interest cooperatives, also in light of the issue of the “social enterprise” regulation.